Melanoma Vaccines and Modulation of the Immune System in the Clinical Setting: Building from New Realities - Madorsky Rowdo, Florencia P.; Lacreu, María L.; Mordoh, José (Frontiers in Immunology, 2012)
To endow the immune system with the capacity to fight cancer has always attracted attention, although the clinical results obtained have been until recently disappointing. Cutaneous melanoma is a highly immunogenic tumor; therefore most of the attempts to produce cancer vaccines have been addressed to this disease. New advances in the comprehension of the mechanisms of antigen presentation by dendritic cells, in the immune responses triggered by adjuvants, as well as the understanding of the role of immunosuppressor molecules such as Cytotoxic T-lymphocyte antigen-4 (CTLA-4), which led to the recent approval of the anti-CTLA-4 monoclonal antibody ipilimumab, have opened new hopes about the installment of immunotherapy as a new modality to treat cancer.